Meningitis caused by extended-spectrum β-lactamase-producing Escherichia coli in infants in France: a case series. Issue 2 (10th April 2023) - Lignieres, Gabriel; Rybak, Alexis; Levy, Corinne; Birgy, André; Bechet, Stéphane; Bonacorsi, Stéphane; Cohen, Robert; Madhi, Fouad
Abstract: Objectives: We report the first case series focusing on clinical and biological characteristics of meningitis caused by ESBL-producing Escherichia coli in infants. Methods: Between 2001 and 2020, data on all cases of E. coli meningitis were prospectively collected from a network of 259 paediatric wards and 168 microbiology laboratories in France. We analysed the clinical and biological characteristics, short-term complications and long-term sequelae of ESBL-producing E. coli meningitis cases in patients <6 months old. Results: In total, 548 cases of E. coli paediatric meningitis were reported. ESBL-producing E. coli represented 12 (2.2%) cases. We included 10 patients aged <6 months old. Eight (80%) patients presented at least one sign of clinical severity: six needed mechanical ventilation, three presented signs of shock and one was in a coma. The overall short-term prognosis was good, with only one meningitis-attributed death in the first hours of care. All surviving children received carbapenems for a median of 21 days (range 9–28). Two relapses occurred, including one in a patient who received only 14 days of imipenem. We reported no long-term sequelae at a median follow-up of 20 months. Conclusions: Meropenem seems to be the treatment of choice for ESBL-producing E. coli meningitis in children and needs to be given as early as possible (<48 h) and for at least 21 days. Maternal colonization or infection with ESBL-producing Enterobacteriaceae needs to be reported to the neonatal or paediatric ICU team, in order to adapt the empirical antibiotic therapy.